Drivers of Indian FDI to Africa – an initial exploratory analysis. Issue 3 (2nd July 2020) - Varma, Sumati; Bhatnagar, Ankur; Santra, Swarup; Soni, Amit
Abstract: This paper attempts to analyse the drivers of the emerging Foreign Direct Investment (FDI) relationship between India and Africa. Using a fixed effect negative binomial model, it examines the determinants of FDI from India to 23 African countries from 2008 to 2016. The study finds that Indian FDI to Africa is a unique combination of both private sector and state driven investment. It is driven by the search for markets, and is pulled despite an adverse business environment. Indian FDI has contributed to several African countries by development of their manufacturing sector and contribution to employment, and has the potential to solve regional problems of poverty and inequality. The paper thus makes a pioneering contribution as an empirical study on OFDI from India to Africa and also to the literature on south – south FDI.